Phytoremediation of lowland soil contaminated with a formulated mixture of Imazethapyr and Imazapic - Souto, Kelen; Avila, Luis; Cassol, Guilherme; Machado, Sérgio Luiz; Marchesan, Enio (Revista Ciência Agronômica, 2014)
The use of plants to decontaminate water and soil contaminated with both organic and inorganic pollutants is a promising technology for sustainable agriculture. The aim of this work was to evaluate the efficiency of plant species in the remediation of formulated mixtures of imazethapyr and imazapic, using the irrigated rice cultivar IRGA 417 as bioindicator. The treatments consisted of the combination of 13 plant species with seven rates of a formulated mixture of imazethapyr and Imazapic (75+25 g e.a. L-1 respectively): 0, 200, 300, 400, 500, 1000 and 4000 mL ha-1. To evaluate the potential for phytoremediation in these species, symptoms of injury and plant height were measured in rice plants at 7, 14, 21 and 28 days after emergence and shoot dry weight at 28 days after emergence. Glycine max, Lolium multiflorum and Lotus corniculatus are potentially promising species in the phytoremediation of soils contaminated with the herbicide imazethapyr and imazapic (up to 4000 mL ha-1), due to being more adapted to hydromorphic environments, which is a feature found in soils cultivated with irrigated rice. Crotalaria juncea, Canavalia ensiformis, Stizolobium aterrimum, Vicia sativa, Raphanus sativus and Triticum aestivum are species capable of the phytoremediation of soils contaminated with imazethapyr + imazapic, however the occurrence of anoxia in hydromorphic soils reduce the establishment and development of these plants.